Greenhouse Fuzzy and Neuro-Fuzzy Modeling Techniques - Efren, Gorrostieta-Hurtado; Carlos, Pedraza-Ortega Jesus; Antonio, Aceves-Fernández Marco; Manuel, Ramos-Arreguín Juan; Saúl, Tovar-Arriaga; Artemio, Sotomayor-Olmedo (IntechOpen, 2012)
None